The icky bug alphabet book - Pallotta, Jerry; Masiello, Ralph; Pallotta, Neil. (New York The Trumpet Club, 1986)
Introduces the characteristics and activities of insects and other crawly creatures from A to Z, beginning with the ant and concluding with the zebra butterfly.
Keywords: Insects -- Juvenile literature; English language -- Alphabet -- Juvenile literature; Insects; Alphabet